Teacher and Students’ Views on The Implementation of Social Science Authentic Learning in Elementary Education - Rulyansah, Afib; Pratiwi, Emy Yunita Rahma; Mariati, Pance (Universitas Nahdatul Ulama Surabaya, 2022)
Abstract: A student's ability to develop essential competencies and attitudes will not be fostered by the use of the traditional educational techniques now used. As a result, teaching methods that engage students in the learning process and encourage them to address real-world issues should be employed in the teaching of Social Science Learning. Teaching social science may benefit from the use of social science authentic learning in this setting. Because students actively participate in the educational process, they encounter real-world challenges and may develop higher-order thinking abilities while addressing difficulties in social science authentic learning, this has been shown to be true. In addition, students are delighted with their education in this manner. We are thus interested in hearing from both students and teachers about their experiences with social science authentic learning in Social Science. The study's sample was created via the use of criteria sampling, which was based on a qualitative research methodology. There are 35 4th grade children, 20 girls and 15 boys, from a private school in Surabaya, Indonesia who participate in the research, as well as the teacher of the class. Focus groups and an open-ended questionnaire were used to gather the data for this study. Using the content analysis method, the data were examined. Authentic social science learning was seen favorably by both students and instructors, according to the findings. Social science authentic learning, according to students, also helped them develop a variety of other characteristics and talents.